The Music in the Churches of the Archbishopric of Granada: The Synod of 1572 - Pérez Mancilla, Victoriano J. (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
In this article we extracted and studied the musical references which appear in the Constitutions of the synod held by the Archbishopric of Granada in 1572. So, first of all there is a historical contextualization of the synodal document, then moving on to analize the musical issues collected in it about the celebration of the mass and the divine service in the temples of the demarcation of Granada, most of them parish. After this, we inserted a chapter heading dedicated to the interpreters of the music in religious cults, which is finally followed by another one with some relevant matters about secular music linked to the churches or to their clergy.